2014
DOI: 10.7314/apjcp.2014.15.13.5293
|View full text |Cite
|
Sign up to set email alerts
|

Salt Processed Food and Gastric Cancer in a Chinese Population

Abstract: To investigate the association between salt processed food and gastric cancer, a hospital based case-control study was conducted in a high risk area of China. One hundred and seven newly diagnosed cases with histological confirmation of gastric cancer and 209 controls were recruited. Information on dietary intake was collected with a validated food frequency questionnaire. Unconditional logistic regression was applied to estimate the odds ratios with adjustment for other potential confounders. Comparing the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 28 publications
2
38
0
6
Order By: Relevance
“…As expected, salt intake was a strong cause of gastric cancer in summary estimates, and Kimchi also showed a strong positive association. Pickled and preserved vegetables were significantly associated with gastric and esophageal cancer in studies conducted in other Asian countries (Jakszyn and González, 2006;Jiang, 2013;Kim et al, 2010;Lin et al, 2014). It is probably because of the salt, but also because of N-Nitrosodimethylamine (Chikan et al, 2012).…”
Section: 3mentioning
confidence: 99%
“…As expected, salt intake was a strong cause of gastric cancer in summary estimates, and Kimchi also showed a strong positive association. Pickled and preserved vegetables were significantly associated with gastric and esophageal cancer in studies conducted in other Asian countries (Jakszyn and González, 2006;Jiang, 2013;Kim et al, 2010;Lin et al, 2014). It is probably because of the salt, but also because of N-Nitrosodimethylamine (Chikan et al, 2012).…”
Section: 3mentioning
confidence: 99%
“…However, the associations between red and processed meat consumption and GC risk have remained inconclusive. Some studies have shown positive associations [6, 7] but others have provided null results [8, 9]. Additionally, there was insufficient evidence for subtype of GC (GCA: gastric cardia adenocarcinoma and GNCA: gastric non-cardiac adenocarcinoma).…”
Section: Introductionmentioning
confidence: 99%
“…Długotrwałe nadmierne spożywanie soli kuchennej sprzyja rozwojowi m.in. chorób układu krą-żenia [11,12] i raka żołądka [13,14]. Zmniejszenie spożycia soli kuchennej jest ważnym działaniem na rzecz poprawy zdrowia publicznego [15].…”
Section: Wprowadzenieunclassified
“…Twarogi kwasowe są produktami o małej wartości energetycznej (98-156 kcal/100 g), bogatymi w pełnowartościowe i łatwo trawione białko (15,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)8 g/100 g) oraz będącymi dobrym źródłem wapnia, fosforu, cynku, witaminy B 2 i B 12 . Produkty te zawierają również lekkostrawny tłuszcz mlekowy, laktozę, kwas mlekowy [18,19].…”
Section: Dyskusjaunclassified